A Randomized Dose-Escalating Phase I Trial of a Replication-Deficient Lymphocytic Choriomeningitis Virus Vector-Based Vaccine Against Human Cytomegalovirus. (21st April 2020) - Schwendinger, Michael; Thiry, Georges; De Vos, Beatrice; Leroux-Roels, Geert; Bruhwyler, Jacques; Huygens, Ariane; Ganeff, Corinne; Buchinger, Heidemarie; Orlinger, Klaus K; Pinschewer, Daniel D; Monath, Thomas P; Lilja, Anders E
Abstract: Background: A vaccine (HB-101) consisting of 2 nonreplicating lymphocytic choriomeningitis virus (LCMV) vectors expressing the human cytomegalovirus antigens glycoprotein B (gB) and the 65-kD phosphoprotein (pp65), respectively, is in development to prevent cytomegalovirus infection. Methods: HB-101 was tested in cytomegalovirus-naive, healthy adults in a randomized, double-blind, placebo-controlled, dose-escalation Phase I trial. Fifty-four subjects received low, medium, or high dose of HB-101 or placebo by intramuscular administration at Month 0, 1, and 3. Safety and immunogenicity were the respective primary and secondary endpoints. Subjects were followed for 12 months after the initial immunization. Results: Vaccination was associated with transient mild to moderate adverse events. HB-101 administration induced dose-dependent gB- and pp65-specific cellular responses, dominated by pp65-specific CD8 T cells, a high fraction of which were polyfunctional. Two administrations were sufficient to elicit dose-dependent gB-binding and cytomegalovirus-neutralizing antibodies (Abs). Cytomegalovirus-specific immune responses were boosted after each administration. Only 1 of 42 vaccine recipients mounted a transient LCMV vector-neutralizing Ab response. Conclusions: HB-101 was well tolerated and induced cytomegalovirus-specific polyfunctional CD8 T-cell and neutralizing Ab responses in the majority of subjects. Lack of vector-neutralizing Ab responses should facilitate booster vaccinations. These results justify further clinical evaluation of this vaccine candidate. Abstract : We described the first-in-man study of a replication-deficient arenavirus-based vector, HB-101, expressing cytomegalovirus gB and pp65. Consecutive administrations of HB-101 were well tolerated and elicited gB-binding and neutralizing antibodies as well as cytomegalovirus-specific CD8 T-cell responses in healthy volunteers.